The Determinants Factor of Dividend Payout Ratio: an Empirical Study of Bank Buku IV in Indonesia - Patricia Yesyurun (Institute of Computer Science (IOCS), 2021)
When it comes to business, for both corporation and shareholders expect a positive return of the investment. Showing profit until paying-out dividend as an indicator of healthy financial performance from banking or non-banking sector will be a proper way to communicate and build positive sentiment to the stakeholders. This study examines the influence variables of financial profitability, risk, collectability and liquidity to determine whether it affects to the dividend policy. By using the panel regression technique with Fixed Effect Model to the Buku IV commercial banks listed in Indonesia Stock Exchange (IDX) of 10 years period from 2010 to 2019 can assess if all the factors significantly or not to the dependent variable of dividend payout ratio. The research distinguishes positive correlation of the profitability and risk factors, not so significant result on the collectability factor and no correlation to the dividend payout ratio. Those factors are represented by independent variables of Net Interest Margin (NIM), Return on Asset (ROA), Capital Adequacy Ratio (CAR), Non-performing Loan (NPL), Loan to Deposit Ratio (LDR). The result indicates that some of the independent variables strongly determine the dividend payout ratio of the banks.